Succession of British citizenzs in Spain after the entry into force of Regulation 650/2012 - Ybarra Bores, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Since the new European successions Regulation entered into force on 17 August 2015, interesting practical issues have arisen: thus, the potential validity of the choice of applicable law to the succession made in testamentary disposition prior to the said date; the attempt to eradicate the traditional practice of making partial wills in Spain in order to dispose the succession of assets located here; or the new doctrine about the requirement to provide certificates of foreign registries of last wills. In this work we will address the current situation of those issues which affect to a greater measure, due to the specificities of their system, the successions opened in Spain which concern to deceased British citizens.
Keywords: international successions; Regulation 650/2012; simpliciter testaments; professio iuris; English Law